Yolk‐Shell‐Structured Nanospheres with Goat Pupil‐Like S‐Doped SnSe Yolk and Hollow Carbon‐Shell Configuration as Anode Material for Sodium‐Ion Storage. Issue 6 (7th May 2021) - Park, Gi Dae; Kang, Yun Chan
Abstract: Rationally nanostructured electrode materials exhibit excellent sodium‐ion storage performance. In particular, yolk–shell configurations of metal chalcogenide@void@C are introduced in various synthetic strategies for use as superior anode materials. Herein, yolk‐shell‐structured nanospheres, with goat pupil‐like configuration of S‐doped SnSe yolks and hollow carbon shells, are synthesized by salt‐infiltration and a simple post‐treatment procedure. Impressively, the co‐infiltration of thiourea and selenium oxide enables the doping of sulfur into SnSe (SnSeS) and carbon shells, as well as the formation of a goat pupil‐like yolk–shell architecture. High‐reactivity thiourea‐derived H2 S gas forms nanocrystals inside the carbon nanospheres. The nanocrystals act as seeds for the crystal growth of SnSeS through Ostwald ripening. The unique yolk–shell structure and composition with a heterointerface provide not only structural stability but also fast electrode reaction kinetics during repeated cycling. The SnSeS@C electrode shows an excellent cycle life (186 mA h g −1 for 1000 cycles at 0.5 A g −1 ) and rate capability (112 mA h g −1 at 5.0 A g −1 ). Abstract : In this study, yolk‐shell‐structured nanospheres, with goat‐pupil‐like configuration of S‐doped SnSe yolks and hollow carbon shells, are synthesized by salt infiltration and a simple post‐treatment procedure, and are applied as an efficient anode material for Na‐ion storage.